2021
DOI: 10.1002/clc.23662
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in acute myocardial infarction—A nationwide German real‐life analysis from 2014 to 2017

Abstract: Background Female sex was reported to be associated with an unfavorable outcome in acute myocardial infarction (AMI). In this nationwide analysis we assessed sex differences in acute outcomes of AMI and recent trends in patient healthcare. Methods We analyzed 875 735 German cases hospitalized with a main diagnosis of ST‐ (STEMI) and non ST‐elevation myocardial infarction (NSTEMI) between January 01 2014 and December 31 2017 regarding morbidity, in‐hospital mortality and treatments. A multivariable logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 39 publications
6
14
0
1
Order By: Relevance
“…On the other hand, several studies in the literature reported a higher mortality rate for female STEMI patients with a less invasive approach, above all in specific socio-economic and cultural areas [7,8]. A German national study showed a 7% increase in in-hospital mortality in STEMI female patients independently from the presence of the main cardiovascular risk factors at baseline [33]. Similar results were reported in a subanalysis of the large SWEDEHEART registry with a higher short-term mortality among female STEMI patients strongly related to age [34].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies in the literature reported a higher mortality rate for female STEMI patients with a less invasive approach, above all in specific socio-economic and cultural areas [7,8]. A German national study showed a 7% increase in in-hospital mortality in STEMI female patients independently from the presence of the main cardiovascular risk factors at baseline [33]. Similar results were reported in a subanalysis of the large SWEDEHEART registry with a higher short-term mortality among female STEMI patients strongly related to age [34].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies showed female STEMI patients had higher in-hospital and external mortality, even among young patients, women with ACS had higher in-hospital mortality than their counterparts [ 7 , 21 24 ]. Consistent with prior investigations, the sex differences among STEMI patients in the in-hospital outcomes were significant in our study, the rates of in-hospital clinical outcomes for women were nearly doubled, and what's more, the rates of adjusted in-hospital clinical outcomes were still higher in women.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect doctors’ attempt not to add another drug to patients who are already poly-treated, as elderly patients often are, and the exacerbation of this attitude during the pandemic may explain the sharp reduction in prescribing rate the over-80s, as well as the higher rate of treatment in younger individuals, where concomitant therapies are less likely. Regarding women, several studies have pointed out a sex-related gap in the treatment for AMI, that encompass timeliness in medical care, pharmacological treatments, and surgical procedures ( Liakos and Parikh, 2018 ; Hao et al, 2019 ; Kuehnemund et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%